An Institutional Work Perspective to Performance Management: The Case of Botswana National Sport Organizations. Issue 1 (2nd January 2023) - Kasale, Lobone Lloyd; Morrow, Stephen; Winand, Mathieu
Abstract: Performance management practices are used by organizations to monitor the efficiency and effectiveness of organizational processes. However, how National Sport Organizations adopt and implement these practices is still unknown. To fill this gap, this research investigates how and why performance management practices are adopted and implemented by National Sport Organizations. Data was collected from documents, 31 semi-structured interviews and five focus group meetings held with 14 Botswana National Sport Organizations and 10 of their stakeholders. The results indicate that stakeholders and individuals within National Sport Organizations play different roles in the creation and maintenance of performance management practices. This information can help sport managers to improve how they implement performance management practices, ensuring the efficiency and effectiveness of their organizational processes and the satisfaction of their stakeholders.